Provision of Qualified Legal Assistance to Individuals Subjected To Covert Operational Investigative Measures in Cases Where These Activities Take Public Forms - V. A. Gusev; E. V. Gerasimenko (Сибирское юридическое обозрение, 2024)
The subject of this study encompasses the legal relations that emerge between citizens and officials within operational units of governmental bodies. Operational investigative activities typically occur covertly, rendering the involvement of a lawyer in such clandestine processes and the provision of qualified legal assistance to individuals subject to secret operational investigative measures impossible. This contravenes the core nature of operational investigative activities, which inherently rely on secrecy and confidentiality. Simultaneously, during the initial covert operational search activities, operational personnel, upon gathering requisite materials and information, reveal their affiliation with law enforcement agencies and proceed to detain a suspected individual. The objective of this study is to delineate the mechanism for safeguarding the right to competent legal assistance for individuals subjected to coercive actions by operational personnel. At the moment of transformation of covert operational investigative measures into public, the rights and freedoms of the person in respect of whom these measures were carried out may be limited and he needs to use the constitutional right to receive qualified legal assistance from a lawyer. The conclusions of the study. During the concluding phases of verification procurement, operational implementation, controlled delivery, and operational experimentation, if a determination is made to decrypt and publicly document the outcomes of operational searches, operational personnel undertake actions that curtail the rights and freedoms of individuals suspected of criminal involvement. Specifically, the following rights are briefly curtailed: the right to freedom of movement; the right to utilize means of communication; the right to inviolability of the home; the right to utilize and manage one's property (buildings, structures, land areas, and vehicles), encompassing objects, substances, and documents therein. The apprehension of a suspected  individual, their personal search, and the inspection of the premises by law enforcement authorities are essential and integrated components of the operational search operation, initially conducted covertly and later transitioning into a public process. In this context, all obtained results should be collectively considered and appraised as the unified outcome of a specific operational search operation, subsequently formalized by an operational officer through a singular protocol detailing the entirety of these operational search activities. Once officials from operational units curtail the right to personal inviolability, freedom of movement, and other constitutional rights and freedoms, the suspected individual must be afforded the opportunity to exercise their right to competent legal assistance, as stipulated in Article 48 of the Constitution of the Russian Federation. Operational staff are required to notify the lawyer of the suspected person and ensure his admission to the place of the operational search activity. A lawyer retains the right to be present at any phase of publicly documenting the outcomes of an operational search operation and, as part of rendering legal assistance, can insist on adherence to the rule of law and provide comments in the protocol.